The Molecular and Mechanistic Insights Based on Gut–Liver Axis: Nutritional Target for Non-Alcoholic Fatty Liver Disease (NAFLD) Improvement - Ji, Yun; Yin, Yue; Sun, Lijun; Zhang, Weizhen (International journal of molecular sciences, 2020)
Non-alcoholic fatty liver disease (NAFLD) is recognized as the most frequent classification of liver disease around the globe. Along with the sequencing technologies, gut microbiota has been regarded as a vital factor for the maintenance of human and animal health and the mediation of multiple diseases. The modulation of gut microbiota as a mechanism affecting the pathogenesis of NAFLD is becoming a growing area of concern. Recent advances in the communication between gut and hepatic tissue pave novel ways to better explain the molecular mechanisms regarding the pathological physiology of NAFLD. In this review, we recapitulate the current knowledge of the mechanisms correlated with the development and progression of NAFLD regulated by the gut microbiome and gut–liver axis, which may provide crucial therapeutic strategies for NAFLD. These mechanisms predominantly involve: (1) the alteration in gut microbiome profile; (2) the effects of components and metabolites from gut bacteria (e.g., lipopolysaccharides (LPS), trimethylamine-N-oxide (TMAO), and N,N,N-trimethyl-5-aminovaleric acid (TMAVA)); and (3) the impairment of intestinal barrier function and bile acid homeostasis. In particular, the prevention and therapy of NAFLD assisted by nutritional strategies are highlighted, including probiotics, functional oligosaccharides, dietary fibers, ω-3 polyunsaturated fatty acids, functional amino acids (L-tryptophan and L-glutamine), carotenoids, and polyphenols, based on the targets excavated from the gut–liver axis.